Autoimmune channelopathies and related neurological disorders. - Vincent, A; Lang, B; Kleopa, K (2006)
Ion channels are crucial elements in neuronal signaling and synaptic transmission, and defects in their function are known to underlie rare genetic disorders, including some forms of epilepsy. A second class of channelopathies, characterized by autoantibodies against ligand- and voltage-gated ion channels, cause a variety of defects in peripheral neuromuscular and ganglionic transmission. There is also emerging evidence for autoantibody-mediated mechanisms in subgroups of patients with central nervous system disorders, particularly those involving defects in cognition or sleep and often associated with epilepsy. In all autoimmune channelopathies, the relationship between autoantibody specificity and clinical phenotype is complex. But with this new information, autoimmune channelopathies are detected and treated with increasing success, and future research promises new insights into the mechanisms of dysfunction at neuronal synapses and the determinants of clinical phenotype.